2019
DOI: 10.1016/j.addr.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-based biomaterials for tissue regeneration

Abstract: Bacteriophage, also called phage, is a human-safe bacteria-specific virus. It is a monodisperse biological nanostructure made of proteins (forming the outside surface) and nucleic acids (encased in the protein capsid). Among different types of phages, filamentous phages have received great attention in tissue regeneration research due to their unique nanofiber-like morphology. They can be produced in an error-free format, self-assemble into ordered scaffolds, display multiple signaling peptides site-specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 183 publications
(357 reference statements)
0
55
0
Order By: Relevance
“…The RGD peptide and GO were operated as adhesion and myogenesis stimulating cues, respectively. Bacteriophages cannot infect and replicate in human cells, so they are a human-safe virus that are potentially applicable in the biomedical field [47][48][49]. GO is among the biofunctional 2D nanomaterials that were reported to possess the ability to stimulate the differentiation of myoblasts.…”
Section: Electrospinningmentioning
confidence: 99%
“…The RGD peptide and GO were operated as adhesion and myogenesis stimulating cues, respectively. Bacteriophages cannot infect and replicate in human cells, so they are a human-safe virus that are potentially applicable in the biomedical field [47][48][49]. GO is among the biofunctional 2D nanomaterials that were reported to possess the ability to stimulate the differentiation of myoblasts.…”
Section: Electrospinningmentioning
confidence: 99%
“…The most promising and thus exploited are filamentous phages, i.e., Ff, f1, Ike, fd, Pf1, and M13. Their length (up to 800 nm) and width (down to 8 nm) are perfect for the synthesis of nanowires and the fibrous components of composites [ 99 , 153 , 154 , 155 , 156 , 157 ].…”
Section: Bacteriophages In Materials Sciencementioning
confidence: 99%
“…phages carrying peptides that stimulate tissue regeneration and the differentiation of cells toward a specific cell type, such as osteoblasts 79,80) or myocytes. 81) For a more in-depth review of this topic, the reader is referred to the recent work of Cao et al 82) As for industry, an interesting example is found in the work of Kim et al, 83) in which the authors, using a phage derived lysin, were able to control, to different degrees, the con-tamination of ethanol-producing yeast cultures by undesired bacteria. Given the relevance of fermentation to industrial processes, any modification that can improve performance could have a significant impact on overall process efficiency and economic viability.…”
Section: Phages In Materials Science and In Dustrymentioning
confidence: 99%